Clinical Pharmacists´ Interventions in the Management of Type 2 Diabetes Mellitus: A Systematic Review - Ismail, Moamen Abdelfadil; Alharbi, Maged Mohammed M; Almusihli, Turki Hamed Naffaa; alqattan, Turki hassan suliman; Alotibi, Fahad Shaag Ibraheem; Asiri, Amnah A; Alsulihim, Kholod Abdullah; Aldoseri, Omamah Saeed; Alrumaih, Nora Saeed; Alobud , Noor Saleh (Journal of Ecohumanism, 2024)
Type 2 diabetes mellitus (T2DM) is a complex metabolic disorder with significant complications that affect quality of life and burden healthcare systems. Despite advances in diabetes management, many patients fail to achieve optimal therapeutic goals, emphasizing the need for innovative, multidisciplinary care approaches. Clinical pharmacists have emerged as key contributors to improving T2DM outcomes.This systematic review assessed the impact of pharmacist-led interventions on clinical, humanistic, and economic outcomes in T2DM management. Two databases, PubMed and the Cochrane Central Register of Controlled Trials, were searched for randomized controlled trials comparing pharmacist-led interventions with standard care. Studies reporting outcomes such as HbA1c, blood pressure, lipid profiles, BMI, medication adherence, health-related quality of life (HRQoL), and economic data were included. Data were synthesized and analyzed for changes from baseline to follow-up.A total of 41 studies involving 6,529 participants were included. Pharmacist-led interventions significantly improved HbA1c (reductions ranging from -0.05% to -2.1%), blood glucose, blood pressure, lipid profiles, and BMI. Improvements in medication adherence were observed in 14 studies, with significant gains in 5. Economic analyses indicated cost-effectiveness, with interventions reducing medical costs and improving quality-adjusted life years (QALYs). However, limited studies reported significant changes in HRQoL.Pharmacist-led interventions demonstrated substantial benefits in improving metabolic control, reducing cardiovascular risks, and enhancing medication adherence in T2DM management. The findings advocate for integrating pharmacists into multidisciplinary teams to optimize diabetes care. Further research on humanistic and economic outcomes is essential to support policy decisions.